Sobre o estatuto epistemológico da racionalidade econômica segundo Karl Popper - Fernandez, Brena Paula Magno; Bêrni, Duilio de Avila (Estudos Econômicos (São Paulo), 2014)
Three types of criticism are currently raised against the acceptance of the rationalityprinciple in economic science. The first relates to the circularity of the reasoning, thesecond concerns the protection of the theory against refutation, and the third – the mostrelevant – concerns the empirical inadequacy of the concept. This article aims to discussthe last criticism, considering the work performed by Popper, in different moments of his career, devoted to determine the epistemological status of the rationality principle.There are three main possible answers to be examined below. The first suggests thatthis postulate be considered as a general law of human behavior. The second requires itto function as an axiom of the theory. Finally, the answer to the third criticism sees therationality postulate as a methodological rule. The article is finished with a statementthat the last solution is a good answer to the core of the above referred criticisms tothe conventional concept of rationality. Therefore it is concluded that, as far as it issituated in a metatheoretical context, the rationality postulate embraces undeniableimportance as a foundation of economic theory. Its absence or non-existence wouldimply the unavailability of instruments leading to the very selection of the empiricaldata designed to submit the theory to tests.